Differences in Urban Residential Property Maintenance by Tenure Type - Rose, Geoff (My University, 2019)
One of the key determinants of the “quality” of a neighbourhood is the extent to which owners maintain their properties. Much has been written about the impact of neighbourhood blight or the physically rejuvenating impact of gentrification. To better understand why some neighbourhoods are thriving, and others not, a critical variable that has seen little exploration is the type of tenure. This thesis, focused mostly on data from the City of Rochester NY, comparing absentee landlords, resident landlords and owner-occupiers, looking for differences in the level of maintenance of residential properties. Using a procedure developed by the author, every house in Rochester, Buffalo, and Syracuse containing 1-6 units was assessed, creating a quantitative analysis that is both more current, and on a much larger scale than previous work. Findings mostly confirmed observations and theories in the literature, but there were a number of significant differences. The key observation within Rochester was that, regardless of geographic scale, absentee owners consistently took the worst care of their properties, followed by resident landlords and then owner-occupiers. Further, size and type of absentee landlord mattered. Tenure was found to be the driving force in predicting maintenance outcomes, compounded by variables such as property values and race. Evidence from Buffalo and Syracuse indicated that findings may be generalizable, at least for declining industrial cities.
Keywords: housing; absentee landlord; resident landlord; residential; Rochester; property maintenance; landlord; tenure; code violations; residential code; tenure type; Buffalo; Syracuse; residential property; slumlord; rental housing; tenant-landlord; urban housing; urban; neighbourhood; neighborhood; homeownership; homeowner; single family home